Abstract：Vocational education plays a significant role in promoting economic transformation and enhancing the adaptability of the labor market. However, its policy design and implementation effects vary significantly across different countries. This study - Song Guanhuai (Journal of Exploration of Vocational Education, 2025)
Abstract：Against the backdrop of new quality productivity, this paper explores the advantages and significance of college counselors providing employment and entrepreneurship guidance to students in the new era. Based on the responsibilities of their roles, the necessity of carrying out such guidance is analyzed. The challenges faced in this process are discussed, leading to a clarification of the role positioning of college counselors. Finally, from the perspective of counselors, strategies for guiding students in employment and entrepreneurship in the new era are investigated.